Determinasi Kepuasan Pelanggan mengenai Citra Merek, Atmosfer dan Harga Pada Restoran Sop Khas Djakarta Bang Rio Kenten di Palembang - satthya putra kosim; Herry Widagdo (Universitas Multi Data Palembang, 2026)
This study aims to examine the influence of Brand Image, Atmosphere and Price on Customer Satisfaction of Sop Khas Djakarta Bang Rio Kenten Restaurant in Palembang partially and simultaneously. The technique used for data collection is by distributing questionnaires with a Likert scale, with a total of 200 respondents based on the Roscoe Formula Method. The type of research used in this study is a quantitative approach. The sampling technique uses non-probability sampling using Purposive Sampling techniques. Data processing of this study uses SPSS 26 software. The results of the study show that brand image has a positive and significant influence, while atmosphere and price have a negative and insignificant influence on customer satisfication.